Exome sequencing identifies a disease variant of the mitochondrial ATP‐Mg/Pi carrier SLC25A25 in two families with kidney stones. Issue 12 (4th August 2021) - Jabalameli, M. Reza; Fitzpatrick, Fiona M.; Colombo, Roberto; Howles, Sarah A.; Leggatt, Gary; Walker, Valerie; Wiberg, Akira; Kunji, Edmund R. S.; Ennis, Sarah
Abstract: Background: Calcium kidney stones are common and recurrences are often not preventable by available empiric remedies. Their etiology is multifactorial and polygenic, and an increasing number of genes are implicated. Their identification will enable improved management. Methods: DNA from three stone‐formers in a Southampton family (UK) and two from an Italian family were analyzed independently by whole exome sequencing and selected variants were genotyped across all available members of both pedigrees. A disease variant of SLC25A25 (OMIM 608745), encoding the mitochondrial ATP‐Mg/Pi carrier 3 (APC3) was identified, and analyzed structurally and functionally with respect to its calcium‐regulated transport activity. Results: All five patients had a heterozygous dominant SLC25A25 variant (rs140777921; GRCh37.p13: chr 9 130868670 G>C; p.Gln349His; Reference Sequence NM_001006641.3). Non‐stone formers also carried the variant indicating incomplete penetrance. Modeling suggests that the variant lacks a conserved polar interaction, which may cause structural instability. Calcium‐regulated ATP transport was reduced to ~20% of the wild type, showing a large reduction in function. Conclusion: The transporter is important in regulating mitochondrial ATP production. This rare variant may increase urine lithogenicity through impaired provision of ATP for solute transport processes in the kidney, and/or for purinergic signaling. Variants found in other genes may compound this abnormality. Abstract : Independently, whole exome sequencing to look for monogenic mutations in two families with autosomally inherited calcium kidney stone disease, identified a disease variant of SLC25A25, encoding the mitochondrial ATP‐Mg/Pi carrier 3 (APC3). Modeling suggests that the variant lacks a conserved polar interaction, which may cause structural instability. Calcium‐regulated ATP transport was reduced to ~20% of the wild type, showing a large reduction in function. This rare variant may increase urine lithogenicity through impaired provision of ATP for solute transport processes in the kidney, and/or for purinergic signaling.